QUASI-GEOSTROPHIC FLOW PAST MOUNTAINS - Ólafsson, Haraldur; Háskóli Íslands (University of Iceland), Veðurstofa Íslands (Icelandic Meteorological Office) and Rannsóknastofa í veðurfræði (Institute for Meteorological Research); haraldur@vedur.is (Croatian meteorological society; info@meteohmd.hr, 2005)
Abstract: Blocked flow at moderate Rossby numbers is studied and an analytic expression is derived for the vertical velocities on each side of the wake: W = (Uo h) / (f Lx Ly) Where Uo is the incoming wind speed, h is the mountain height, f is Coriolis parameter, Ly is mountain half-width and Ly is a length scale of the vertical mortion downstream of the edges of the mountains. To illustrate the use of the above expression, a collection of flows over Iceland is presented and the calculated vertical velocities are compared to the number of days with precipitation in two different regions.